The Hydraulic and Environmental operation for the Main Outfall Drain, Ad Dalmaj Lake and Al Hammar Marsh System - Muhannad J. Al Kazwini; Mahmoud S. Al Khafaji; Khulood J. Hussain (Engineering and Technology Journal, 2013)
Iraqi Marshlands which are located within the southern part of Iraq were dried after 1991. The dried marshes were re-flooded after year 2003. Because of the shortage of water that feeds the marshes during the last years, these marshes began to dry again. Therefore, finding new feeding sources became very necessary matter. The Main Outfall Drain, MOD, is suggested to be one of these sources to feed Al Hammar Marsh during the dry water years. Ad Dalmaj Lake which is located upstream of Al Hammar Marsh is mainly feeding by the MOD water and then the outfall of this lake is discharge again into the MOD. Therefore, the hydrological operation of this lake and then the quantity and quality of the outflow water from this lake into the MOD affected the water quality of Al Hammar Marsh when using the MOD water to feed the marsh. A hydrological and water quality routing model was prepared based on mass conservation low, mass balance model, and two scenarios were applied for Ad Dalmaj Lake feeding, constant inflow with variable outflow and constant outflow with variable inflow, based on the incoming and outgoing discharges. Each scenario includes six cases of lake maximum inundation area; 100%, 90%, 80%, 70%, 60% and minimum inundation. For each case the inundation area varied with respect to the ET0 variation from minimum area during the month of maximum ET0 to maximum area, of this case, during the month of minimum ET0. TDS concentration was used as a measure of the salinity of the water because it fairly indicates the level of salinity problem. The variation of inflow and outflows discharges, water level, lake and marsh area, storage volume, and the water salinity within the lake and marsh were Results of applying these models with these flow scenarios and inundation cases show that the water salinity within Ad Dalmaj Lake and Al Hammar Marsh was out of the acceptable range of international standards for most of the studied cases. While for other cases it was unpalatable for drinking, several restrictions must be imposed when used for irrigation to prevent salts effects on crops, soil, and ground water, and not acceptable for livestock and unfit for poultry in most of the months during two operation years and in some months in the beginning of the first year, the water can be used for growing livestock and poultry.